2007
DOI: 10.1002/chin.200719054
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tetrathiacalix[4]arene Functionalized by Acetylhydrazone Fragments.

Abstract: Calixarenes O 0450 Synthesis of Tetrathiacalix[4]arene Functionalized by Acetylhydrazone Fragments. -(PODYACHEV*, S. N.; SUDAKOVA, S. N.; SYAKAEV, V. V.; SHAGIDULLIN, R. R.; GALIEV, A. K.; KONOVALOV, A. I.; Mendeleev Commun.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…18 This study showed that the high extraction ability of these compounds com pared to that of their structural unit, namely, 4 tert bu tylphenoxyacetylhydrazide, is caused by the preorganiza tion of the hydrazide groups on the calixarene platform resulting in the positive cooperative effect in binding of metal ions. An important influence of the cooperative effect of the functional groups on the catalytic properties was observed 26 for the supramolecular models of enzymes.…”
mentioning
confidence: 97%
“…18 This study showed that the high extraction ability of these compounds com pared to that of their structural unit, namely, 4 tert bu tylphenoxyacetylhydrazide, is caused by the preorganiza tion of the hydrazide groups on the calixarene platform resulting in the positive cooperative effect in binding of metal ions. An important influence of the cooperative effect of the functional groups on the catalytic properties was observed 26 for the supramolecular models of enzymes.…”
mentioning
confidence: 97%